Determinants of Family Planning Method Use in Ilala Municipality, Dar es Salaam, Tanzania - David Msokwe (New Ideas Concerning Arts and Social Studies Vol. 1, 2025)
The widespread adoption of family planning methods (FPMs) represents one of the most dramatic changes of the 21st century. The growing use of contraception worldwide has increased the ability of couples to choose the number and spacing of their children and to have tremendous lifesaving benefits. This paper examines the use of family planning methods in Ilala Municipality, Dar es Salaam, Tanzania. A total of 55 respondents were involved in the study. The study used both quantitative and qualitative techniques in collecting and analysing data. A questionnaire, in-depth interviews and documentary review were used to gather data. In-depth interviews with eleven including seven key officials, two street chairpersons, and two shop FPMs vendors were conducted to fill the study purposes. The analysis of data obtained from the survey was analysed using a statistical tool known as Statistical Package for Social Sciences (SPSS version 20). The findings indicated that modern family planning methods, such as condoms and oral contraceptives like postinor-2, morning-after pills, injection, and implants, were preferred over traditional family planning methods, such as withdrawals, calendar rhythm method and periodic abstinence. The factors influencing family planning methods were education, access to information, fear and unfounded ethical beliefs, number of siblings, children as an indicator of one’s high status, prestige, and children confirming one’s virtue. The trend of Traditional Family Planning Methods (TFPM) and Modern Family Planning Methods (MFPM) indicates an increase in the positive perception of the MFPMs to both educated and uneducated users. Generally, the use of family planning methods was determined by the socio-economic status of the users and environmental variables. Therefore, it is recommended that the stakeholders construct health centres and educate people on good family planning methods.